O trabalhar com médicos obstetras - Barbosa, Jéssika Sonaly Vasconcelos (2016)
Obstetrics is a prominent area for Medicine because it represents one of the basic needs of the population. It is responsible for a very important social, cultural and historical event that is the realization of a childbirth. This submits the professionals who work in this area to a constant pressure for good results, in addition to the variability and dilemmas that are inherent in the profession. Thereby, the present dissertation has as the main objective to understand the work of Obstetricians engaged in a public maternity. In order to do that, the theoretical contribution of this study is based on the contributions from Psychodynamics of Work through reflections brought by Christophe Dejours. Regarding the method, this research presents a field study of a qualitative nature. The techniques used here were semi-structured interviews and observations of the work. The perspective adopted for data analysis was the thematic content analysis. In this research, 13 obstetricians working in a maternity unit located within the Northeast region participated, being 10 female and 3 male. Their ages ranged between 31 and 61 years old. Regarding the time of practice as an obstetrician, it ranged from one year up to 40 years of experience in the job. As a result, it is highlighted the presence of collective work in the activity of an obstetrician. Working together is present in the professional performance and as a professional training. The development of practical intelligence, subjective mobilization and, above all, cooperation, are presented as necessary to ensure that the obstetrician performs his or her job and win the hurdles imposed by the real. In addition to the health risks inherent in this professional category, obstetricians deal daily with violence from the doctor-patient relationship, in which they suffer threats from the recipients of their service, in an ambiguous relationship, sometimes made of difficulty and brainstorm, and in other times made of pleasure, satisfaction, and recognition. Furthermore, another highlight is the presence of subjecting activity in the work of an obstetrician; in order to work, the obstetrician needs to incorporate the world. In addition, the use of time away from duty is permeated by work, giving little room for family relationship, leisure activities and health care. Finally, despite the difficulties, obstetricians are fulfilled and they show that the profession makes gains for their identity and self-realization.